Synthesis, Antimicrobial Evaluation and QSAR Studies of Some Newly Synthesized Imidazole Derivatives - Tarun Virmani, Pooja Sharma (International Journal of Advanced Science and Technology, 2020)
In the present study a series of imidazole derivatives were synthesized having antimicrobial activity and were subjected to QSAR analysis. the parameters of QSAR analysis indicates antimicrobial activity of to be synthesized imidazole derivatives, it has been found that compound SP1and SP2 are found to be most potent antimicrobial agents, 2D-QSAR gives a revealed and validated model to predict a potent compound.